CONTESTING THE AUTHENTICITY OF ABU HURAIRAH’S MISOGYNISTIC HADITH: Bennett and Mernissi’s Critical Perspectives (RIWAYAH, 2025)
The critique of Prophet Muhammad’s originality, both historical and theological, has long been a central concern among Orientalist scholars challenging the authenticity of Islam. Clinton Bennett, a Christian theologian, presents himself as a Western academic adopting an independent stance in evaluating the rationale behind Muhammad’s teachings. While acknowledging the canonical status of Sahih al-Bukhari, Bennett questions the reliability of Abu Hurairah as a hadith transmitter, arguing that the honorific title Amir al-Muʾminin is inappropriate for a narrator of misogynistic traditions. His critique aligns with feminist scholar Fatima Mernissi’s gender-sensitive readings, particularly her concerns regarding the authenticity of certain historical narratives. A prominent example is Abu Hurairah’s narration of a woman condemned to hell for neglecting a female cat, an account interpreted as symptomatic of misogynistic tendencies within Islamic tradition. This study explores the authenticity of such a hadith and its implications for understanding misogyny in Islamic discourse through an inclusive and analytical lens. Employing a qualitative, descriptive-analytical method, it addresses the following question: How do Orientalist and feminist methodologies evaluate the authenticity of misogynistic hadiths in relation to Abu Hurairah’s credibility? The findings reveal that both Bennett and Mernissi assess Abu Hurairah’s reliability through a historical-critical framework, focusing on his age, proximity to the Prophet, and personal character. Their shared conclusion positions him as a junior companion whose close access to the Prophet arguably enabled a more consistent and guided transmission of hadiths. [Kritik orisinalitas posisi Nabi mengenai identitas historis dan teologisnya, menjadi salah satu perhatian Orientalis dalam menggugat otentisitas Islam. Clinton Bennettt sebagai teolog Kristen berupaya memposisikan dirinya sebagai akademisi Barat yang independen dalam mengkritisi nalar ajaran Muhammad. Pengakuan dirinya atas orisinialitas Sahih al-Bukhari, menemukan bantahan atas keadalahan Abu Hurairah sebagai sahabat Nabi. Karena, predikat gelar Amir al-Mukminin tidak selayaknya disematkan kepada perawi hadis misoginis. Tuduhan Bennettt, berpihak atas kontribusi stereotip gender tokoh Feminis, Fatimah Mernissi dalam mempertimbangkan otentisitas narasi sejarah. Pernyataan Abu Hurairah, menarasikan peristiwa masuknya seorang perempuan ke dalam neraka atas perbuatan menelantarkan kucing betina. Penelitian ini membuka ruang eksplorasi dalam mendialogkan oetentisitas hadis tersebut secara inklusif dan analitis terkait pemahaman misoginis dalam tradisi Islam. Metode penelitian yang digunakan kualitatif yaitu deskriptif analitis. Permasalahan akademis yang muncul dalam bentuk pertanyaan penelitian yaitu bagaimana metode autentisitas hadis misoginis perspektif Orientalis dengan Feminis dalam meniai menilai kredibilitas Abu Hurairah sebagai perawi misoginis?. Hasil penelitian menunjukkan bahwa keduanya menilai kredibilitas Abu Hurairah melalui analisis pendekatan Kritik sejarah dengan menguraikan fakta historisitas usia, aksebilitas perawi serta karakter. Pandangan Bennett dan Mernissi terhadap Abu Hurairah sebagai golongan sahabat junior lebih konsisten dalam melestarikan periwayatan hadis, sebab dalam bimbingan nabi yang lebih intens].